2022
DOI: 10.1371/journal.pone.0262430
|View full text |Cite
|
Sign up to set email alerts
|

A value-based model of job performance

Abstract: This agent-based model contributes to a theory of corporate culture in which company performance and employees’ behaviour result from the interaction between financial incentives, motivational factors and endogenous social norms. Employees’ personal values are the main drivers of behaviour. They shape agents’ decisions about how much of their working time to devote to individual tasks, cooperative, and shirking activities. The model incorporates two aspects of the management style, analysed both in isolation a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
2
4
0
1
Order By: Relevance
“…As we saw earlier, the interaction of reward interdependence and task interdependence jointly affected performance. Cooperation was solely influenced by task interdependence (consistent with Roos et al, 2022). However, the effect of cooperation on performance is moderated by reward interdependence, having no effect when rewards are individual.…”
Section: Free Ridingsupporting
confidence: 59%
See 2 more Smart Citations
“…As we saw earlier, the interaction of reward interdependence and task interdependence jointly affected performance. Cooperation was solely influenced by task interdependence (consistent with Roos et al, 2022). However, the effect of cooperation on performance is moderated by reward interdependence, having no effect when rewards are individual.…”
Section: Free Ridingsupporting
confidence: 59%
“…Similar results were found by Aakvik et al (2017), who concluded that team processes which included an element of pressure enhanced cooperation, and that feedback on team and individual performance contributed to better performance under team incentives than individual ones, and consequently that "free-rider effects are not a serious problem" (p.117), at least in the customer service center that they studied. Amongst the non-field studies, Ladley et al (2015), using an agent-based model akin to Roos et al (2022), also show that free riding does not survive peer pressure, at least in the medium-to long-term. They compare groups selected and rewarded on the basis of group performance, which are therefore heterogeneous, with groups composed on the basis of individual performance who are rewarded individually.…”
Section: Free Ridingmentioning
confidence: 99%
See 1 more Smart Citation
“…Por ejemplo, si la escuela paga la capacitación; Construir la organización y las relaciones. En este tipo de colaboración, se posibilita un fuerte compromiso con la organización por parte de los empleados que se sienten valorados por la organización que les dio la oportunidad o el regalo que recibieron, (Ross, Reale y Banning, 2022).…”
Section: Compromiso Normativounclassified
“…These values can influence an individual's career choices, job satisfaction, and overall engagement with their work (Baranik et al ., 2022). Recent literature delineates Extrinsic Rewards, Intrinsic Rewards and Job Security as constituents of Work Values that drive behaviour aligned with societal and environmental well-being (Roos et al ., 2022; Venketsamy and Lew, 2022).…”
Section: Introductionmentioning
confidence: 99%